Heterogeneity in esophageal and gastric cardia precursor progression during six‐year endoscopic surveillance after population‐based screening in a Chinese high‐risk region - Wen, Denggui (Thorac Cancer, 2017)
BACKGROUND: The study was conducted to examine esophageal and gastric cardia precursor progression. METHODS: After population‐based baseline screening, 145 precursor and 335 chronic inflammation cases were endoscopically surveyed for six years. RESULTS: Surveillance of interval and baseline diagnoses for 18 severe dysplasia (SD) cases later detected were: 13, 23, 39, and 44 months since a diagnosis of chronic inflammation in four cases; 6, 6, 6, 11, 13, 16, 16, and 23 months since mild dysplasia (mD) diagnoses in eight; and 6, 9, 10, 13, 18, and 48 months since moderate dysplasia (MD) diagnoses in six. Rates for 11 carcinoma in situ (Cis) cases later detected were: 7 and 18 months since basal cell hyperplasia (Bch) diagnoses in two; and 6, 6, 9, 13, 13, 18, 35, 44, and 50 months since MD diagnoses in nine. In 10 cancer cases later detected, rates were: 6, 6, 7, 18, 19, 34, 36, and 48 months since SD diagnoses in eight cases with submucosal carcinoma; 46 months since MD diagnosis in a T (2) N (0) M (0) carcinoma case; and 52 months since Bch diagnosis in another T (2) N (0) M (0) case. CONCLUSION: Esophageal and gastric cardia precursors are heterogeneous. Male gender, advanced age, family history of upper gastrointestinal cancer, and multifocal dysplasia are significant independent predictors for progression, and Bch/mD, MD, and SD constitute three distinctive entities regarding the risk of cancer.